"Locals" and "Cosmopolitans": On the Productivity of Scholars. Issue 4 (4th July 2019) - Gavrilova, E. V.; Ushakov, D. V.; Iurevich, A.V.
Abstract : An analysis is provided of the results of a study of the scholarly productivity of Russian doctors of science in the middle generation who work within the Russian Academy of Sciences system. We show that the scholars' achievements on the international versus domestic Russian arenas are not only different, but are also only weakly related. This gives reason to conclude that the competencies and social capital of scholars that facilitate their achievements inside the country and abroad are different, and sometimes even alternatives to each other. We also reveal that scholarly citation indexes are insufficient to evaluate domestic Russian achievements by scholars, while the evaluation of their international achievements is much more accurate.